Language, Communication, and Meaning in a Multicultural Context - Damayanti, Sri; Tajuddin, Tajuddin; Azis , Fatimah (Universitas Cokroaminoto Palopo, 2025)
This article presents a narrative literature review on language, communication, and meaning in multicultural contexts. Drawing on work in intercultural communication, intercultural pragmatics, discourse analysis, and multimodality, it explains how cultural frameworks shape communicative norms and expectations, and how meaning is negotiated across linguistic and cultural boundaries. The review highlights the importance of pragmatic competence, including awareness of speech acts, politeness strategies, and contextual inference, for successful intercultural interaction. It also considers discourse-analytic and multimodal perspectives on identity construction and power relations, particularly in digital and globalized environments. Deardorff’s process model of intercultural competence is used to show how attitudes, knowledge, and skills support effective and appropriate communication. The article proposes an integrative conceptual model that connects cultural frameworks, semiotic resources, interactional practices, and intercultural competence as key components of meaning-making. Implications are discussed for language and teacher education, organizational communication, and future research on multicultural encounters.